2019
DOI: 10.1155/2019/1614963
|View full text |Cite
|
Sign up to set email alerts
|

Classification and Assessment of the Patelar Reflex Response through Biomechanical Measures

Abstract: Clinical evaluation of the patellar reflex is one of the most frequent diagnostic methods used by physicians and medical specialists. However, this test is usually elicited and diagnosed manually. In this work, we develop a device specifically designed to induce the patellar reflex and measure the angle and angular velocity of the leg during the course of the reflex test. We have recorded the response of 106 volunteers with the aim of finding a recognizable pattern in the responses that can allow us to classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Other devices have also been used to evaluate the PTR response. An accelerometer was used to demonstrate the difference between myelopathy patients and healthy volunteers in terms of the PTR response 7 , and another study reported an accuracy of 89.62%, according to the NINDS score, using machine learning classifiers 30 . A motion capture system was also used to demonstrate the knee angle increase dependent on the tapping force in healthy participants 15 , 16 and its usability for cerebral palsy patients 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Other devices have also been used to evaluate the PTR response. An accelerometer was used to demonstrate the difference between myelopathy patients and healthy volunteers in terms of the PTR response 7 , and another study reported an accuracy of 89.62%, according to the NINDS score, using machine learning classifiers 30 . A motion capture system was also used to demonstrate the knee angle increase dependent on the tapping force in healthy participants 15 , 16 and its usability for cerebral palsy patients 31 .…”
Section: Discussionmentioning
confidence: 99%
“…4 Pathological alterations in these reflexes are important signs of neurological diseases and distinguishing between delayed or exaggerated PTR responses may help to detect neurological disorders. 5 , 6 The reflex latency and amplitude of PTR response may vary in people with neurological, neuromuscular, and endocrine disorders. 7 , 8 Therefore, observation of irregularities in kinematics of tendon refelexes provides valuable insight into the diagnosis and prognosis of the patient's neurological condition.…”
Section: Introductionmentioning
confidence: 99%